2021
DOI: 10.1007/s12603-020-1479-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serum 25(OH) Vitamin D Level on Mortality in Patients with COVID-19 in Turkey

Abstract: Background: Because of the lack of sufficient data, we aimed to investigate the role of serum 25(OH) vitamin D level on COVID severity and related mortality. Methods: This was a retrospective observational study. Data, including sociodemographic features, clinical characteristics, and laboratory data, and 25(OH) vitamin D levels were recorded for each study participant. Patients were stratified into different vitamin D groups; Normal (Serum 25(OH) vitamin D level >30 ng/mL), Vitamin D insufficiency (21-29 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 32 publications
4
93
2
8
Order By: Relevance
“…In contrast, D-dimer concentrations were moderately associated with 25(OH)D concentrations ( r = 0.437, P < 0.05) ( 61 ). Karahan and Katkat ( 54 ) in their retrospective study in 149 COVID-19 patients found a significant negative relation between serum 25(OH)D concentration and CRP ( r = −0.253, P = 0.002). Kerget et al ( 50 ) found a significant negative correlation only with CRP ( r = −0.297, P = 0.01), but not IL-6, ferritin, and D-dimer.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In contrast, D-dimer concentrations were moderately associated with 25(OH)D concentrations ( r = 0.437, P < 0.05) ( 61 ). Karahan and Katkat ( 54 ) in their retrospective study in 149 COVID-19 patients found a significant negative relation between serum 25(OH)D concentration and CRP ( r = −0.253, P = 0.002). Kerget et al ( 50 ) found a significant negative correlation only with CRP ( r = −0.297, P = 0.01), but not IL-6, ferritin, and D-dimer.…”
Section: Resultsmentioning
confidence: 94%
“…Among 15 studies that assessed the relation between mortality and VDD, 13 studies were included in the analysis. Pooled analysis of 4 adjusted studies that used the Cox survival method ( 13 , 51 , 56 , 60 ) (HR: 2.35; 95% CI: 1.22, 4.52; I 2 : 84%; Figure 4 A ) and 5 studies ( 44 , 47 , 53 , 55 , 62 ) with crude OR (OR: 2.62; 95% CI: 1.13, 6.05; I 2 : 47.8%; Figure 4B ) indicated a significant association of VDD with mortality, while in adjusted studies that used logistic regression ( 54 , 59 , 65 ), no relation was observed (OR: 1.05; 95% CI: 0.63, 1.75; I 2 : 76.6%). Two studies were not included in the analysis since 1 study had an RCT design ( 36 ) and another one used different statistical methods ( 64 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Besides this, it has crucial regulatory roles in the adaptive and innate immune systems 4 . It was shown that vitamin D deficiency is quite common among COVID‐19 patients 5 . A recent clinical study showed that COVID‐19 patients supplemented with vitamin D had less severe symptoms of the disease 6 …”
Section: Introductionmentioning
confidence: 99%